Problems with Health Services and Assessment of Telehealth needs for Peritoneal Dialysis: Patient, Caregiver, and Health Professional’s Perspectives - Rattana-umpa, Nattaya; Sriyuktasuth, Aurawamon; Jeungsmarn, Piyatida (Nursing Science Journal of Thailand, 2022)
Purpose: To explore health service problems and assess the needs toward telehealth for peritoneal dialysis in patients undergoing continuous ambulatory peritoneal dialysis, caregivers, and health professionals. Design: Mixed methods study. Methods: A quantitative part was conducted in the first phase to explore health service problems in patients with peritoneal dialysis and telehealth needs in 200 patients/caregivers and 28 health professionals. Data were collected using three questionnaires including 1) personal information form, 2) dialysis health service problem questionnaire, and 3) telehealth needs questionnaire. Descriptive statistics, independent t-test, and one-way ANOVA were applied for data analysis. In the second phase, the researchers conducted focus groups among patient, caregiver, and health professional groups to gain further insights from the data obtained in the first phase. Data were analyzed by using content analysis. Main findings: The patients/caregivers reported health service problems at a moderate level and overall needs for telehealth at a high level. For health professionals, they identified problems in providing health services and needs for telehealth at high levels. Main care features suggested from all groups included resources for knowledge and skills related peritoneal dialysis and self care, communication channels in various forms, notifications of abnormalities and treatment dues, dialysis fluid follow-up, and recording/monitoring health and dialysis related information. Conclusion and recommendations: Health services for patients undergoing continuous ambulatory peritoneal dialysis in Thailand are currently a challenge for health problem management of the country. Developing a health service that meets the needs of all key stakeholders by using information technology may improve service efficiency and health outcomes in this population group.